Slaying the Embodiment of Lust: A Painting of a Martyr-Monk Vanquishing a Female Demon - Szymańska, Agnieszka E. (Journal of early Christian studies, 2025)
The seventh-century painting of Sisinnios and Alabasdria from the Monastery of Apa Apollo at Bawit, Egypt, depicts an equestrian saint spearing a female demon. Previous scholarship has established connections between the mural’s iconography and the imagery of holy rider amulets. This article expands on those discussions and probes the painting’s function as a talisman that bolstered its monastic beholders’ defenses against demonic assaults. In a departure from earlier scholarly treatments of the mural, I explore how, to male monastic practitioners, the image of Alabasdria did not merely represent a demonic murderer of babies but also embodied lust. According to textual sources, women seduced monks, and Alabasdria’s sensual depiction could also attract the monks’ gaze. The inclusion of a centaur, a hybrid creature connoting hypermasculinity and lasciviousness, affirms the painting’s erotic dimension. Finally, this article examines the mural through the intersection of sex, violence, and gender. Imaginatively entering the image empowered monks to become Sisinnios, slay the embodiment of lust, and ultimately subjugate their libidos. The painting called monastic practitioners to imitate Sisinnios murdering a sexualized woman, fueling the prejudice against femininity, which male writers vilified as a threat to the ideal ascetic life.